2012
DOI: 10.1177/1759720x12444175
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone morphogenetic proteins in ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS), the best-known form of spondyloarthritis (SpA), is a remodelling arthritis characterized by chronic inflammation and bone formation. Ankylosis of the axial skeleton and sacroiliac joints leads to an impairment of spinal mobility, progressive spinal fusion and an increased risk of spinal fractures. The nature of the relationship between inflammation and new bone formation in AS has been controversial and questions remain as to whether there is a direct relationship between inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…It has been shown that the molecular pathways underlying AS recapitulate the presence of endochondral bone formation, where BMPs play a key role (63). Similar to their role in artery plaque formation during atherosclerosis, type II diabetes, and aortic valve disease, inflammatory cytokines are strongly suspected to induce ectopic bone formation (6466).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the molecular pathways underlying AS recapitulate the presence of endochondral bone formation, where BMPs play a key role (63). Similar to their role in artery plaque formation during atherosclerosis, type II diabetes, and aortic valve disease, inflammatory cytokines are strongly suspected to induce ectopic bone formation (6466).…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used for treating limb bone defect diseases caused by trauma and tumor, congenital malformation, bone infection, etc. [32].…”
Section: Bone Transportation and Bone Lengtheningmentioning
confidence: 99%
“…Vertebral osteoporoz AS'in tanınmış bir özelliğidir ve bu durum omurganın biyomekaniğini değiştirerek kırılmalara karşı artmış bir duyarlılık meydana getirir (4,5). Dolayısıyla AS' li kişiler vertebra kırığı riski ile karşı karşıya kalmaktadırlar (6)(7)(8).…”
Section: Olgu Sunumuunclassified